Investigation of rs80356932 of BRCA1 Gene and Other Physiological Factors with Benign Breast Disease (Journal of Fatima Jinnah Medical University, 2024)
Background: Benign Breast Diseases (BBD) are a diverse group of conditions characterized by abnormal breast morphology and lesions which may be caused by both genetic and environmental factors as well as infectious agents such as bacteria and viruses. Since it is generally accepted that these conditions do not usually pose a risk for breast cancer so a small amount of information is available about them. Present study undertook the investigation of the association of various factors with benign breast disease, including family history, history of abortions, tumors in other organs of the body, menopausal status, and rs80356932 variant of the BRCA1 gene.  Patients and Methods: This case control study included 91 patients of BBD and 100 normal individuals at Services Institute of Medical Sciences and Jinnah Hospital from July 2021 to July 2022. Demographical and clinical data was collected with the help of a pre designed form, and blood sample was also collected with informed consent. Tetra-ARMS-PCR was performed on DNA extracted from these samples to determine the genotype of rs80356932. Chi-square test of independence was used via SPSS version 22 for the measurement of association.Results: The results reported that the family history, menopause status, history of abortions and tumor in any other organ of the body were found to be significantly associated with benign breast tumor/ disease (P-value
Keywords: Benign breast tumors; Polymorphisms; Polymerase chain reaction